Alumina Ceramics : Biomedical and Clinical Applications - Ruys, Andrew J. (Woodhead Publishing series in biomaterials., 2019)
Alumina Ceramics: Biomedical and Clinical Applications examines the extraordinary material, Alumina, and its use in biomedicine and industry. Sections discuss the fundamentals of Alumina Ceramics, look at the various industrial applications, and examine a variety of medical applications. Readers will find this to be an invaluable and unique resource for researchers, clinical professionals, engineers, and advanced level students. Alumina ceramics are a leading biomaterial used for specialist medical applications, such as bionic implants and tissue engineering, and the only biomaterial commercially viable for use as bearings for orthopedic hip replacements. As such, this book is a timely resource on the topics discussed.